Common Cycles in Commodity Prices - Uzuner, Gizem (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This study empirically investigates the short- and long-run co-movement among commodity prices using six commodity group price indices. The commodity group indices used in the study include foodstuffs, livestock and products, fats and oils, raw industrials, metals and textiles. The data for this study was sourced from Commodity Research Bureau (CRB); the frequency of the data is monthly and covers the period from 1951M1 to 2015M6. In order to investigate the short- and long-run co-movement properties of the commodity prices, the study employs the unit root tests, Granger causality test, Johansen cointegration test as well as common cyclical features test. The study reveals that all the variables are stationary in first differences with KPSS test, i.e., all the variables are integrated of same order, I (1). The Granger causality test shows that all variables have at least one unidirectional Granger causality. Johansen cointegration test suggests three cointegration vectors, thus implies long-run equilibrium relationship among the groups of commodity prices. The study shows two common cycles among the groups of six commodity price indices based on the common cyclical features test. The major implication from the findings of the study is that short- and long-run changes in the commodity prices of interest are driven by common factors and any observed change in price of one of the selected commodity prices implies that the other will also change both in the short- and long-run. Therefore, the history of one of the commodity prices can be utilized to make prediction for the others. Keywords: Common cycles, commodity prices, co-movement.

ÖZ: Bu çalışma ampirik olarak, seçilmiş çeşitli emtiaların fiyatlarındaki kısa dönem ve uzun dönem birlikte hareketleri analiz etmektedir. Çalışmada kullanılan veri seti Emtia Araştırma Bürosu veri tabanından temin edilmiş ve 1951 yılı Ocak ayından 2015 yılı Haziran sonuna kadar olan veriler kullanılmıştır. Çalışma hedeflerine uygun olarak, birim kök testleri, Granger nedensellik testi, Johansen eştümleşme testi ve ortak özellikler döngüsellik testi kullanılmıştır. Birim kok testi sonuçları (KPSS testi) tüm değişkenlerin ilk gecikmede durağan olduğunu göstermektedir. Kısacası tüm değişkenler I(1) düzeyinde tümleşiktir. Granger nedensellik testi de tüm değişkenler arasında en az bir yönlü Granger nedenselliğinin varlığına işaret etmektedir. Johansen eştümleşme testine göre de üç eştümleşme vektörü bulunmakta ve emtia fiyatları arasında uzun dönem ilişkiye dikkat çekilmektedir. Çalışma bulgularına göre ortak döngüsellik testi emtia fiyatları arasında iki ortak döngüye işaret etmektedir. Çalışma sonuçları, emtia gruplarının geçmiş yıllardaki verilerinin tahmin için kullanılabileceği hipotezinin desteklendiğini, dolayısıyla seçilmiş emtia gruplarındaki fiyat değişimlerinin uzun ve kısa dönemde birbirlerini etkilediklerini göstermektedir. Anahtar kelimeler: Ortak döngü, Emtia Fiyatları, Birlikte Hareket
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2016. Supervisor: Prof. Dr. Mehmet Balcılar.
Keywords: Economics; Commodities-Investment Economics; Prices-Sources; Common cycles; commodity prices; co-movement